Replacement of Coarse Aggregate with Locally Available Brick Aggregate - Bangwar, D. K.; Saand, A.; Keerio, M. A.; Soomro, M. A.; Laghari, A. N. (Engineering, Technology & Applied Science Research, 2017)
Due to the abundant usage of concrete as a construction material, there is a fast dwindling source of aggregates. There are regions where there is scarcity of coarse aggregate, so to resolve this problem, Bricks Aggregates (BAs) can be used as coarse aggregate. A concrete mix ratio of 1:2:4 having characteristics strength of 3000 psi has been used in this experimental work. Compressive and tensile strength of concrete mix where 50% coarse aggregate is replaced with brick aggregate and concrete mix where 100% coarse aggregate is replaced with brick aggregate and addition of silica fume as a supplementary cementing material have been evaluated at 7, 14 and 21 days of age. The experimental test results revealed the compressive and tensile strength of concrete where coarse aggregate is replaced at 50% is almost the same as that normal concrete at the 7, 14, 21 and 28 days.